Sofrimento psíquico dos trabalhadores de saúde mental em contexto pandêmico e fatores associados - Stander, Ana Luisa Camachi [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Objective: To analyze the factors associated with psychological distress in exposure to COVID in mental health workers. Method: Cross-sectional research with 108 workers from four mental health services in a city in the interior of São Paulo.Data: collect conductedd online between October and December 2020 through a sociodemographic questionnaire and the Self Report Questionnaire-20 Scale (SRQ-20). Descriptive analysis and multiple linear regression of ordinary least squares were performed, searching for associated factors for the variation in the scale score. Results: It presented a high mean in mental illness (15.07), in relation to a cutoff score of 07 points, and an association was found between being followed up in mental health and lower scores of psychological distress. Conclusion: Monitoring in mental health for professionals exposed to COVID is an important coping strategy for the overload and change in the work logic during and after the pandemic, which seems to be associated with psychological distress.

Objetivo: Analisar os fatores associados de sofrimento psíquico na exposição ao COVID em trabalhadores de saúde mental. Método:Pesquisa transversal, com 108 trabalhadores de quatro serviços de saúde mental de um município do interior Paulista. Coleta de dados realizada online entre outubro e dezembro de 2020 por meio de questionário sociodemográfico e Escala Self Report Questionnaire-20 (SRQ-20). Realizado análise descritiva e regressão linear múltipla de mínimos quadrados ordinários, em busca de fatores associados para a variação no escore da escala. Resultados: Apresentou média alta no adoecimento psíquico (15,07), em relação a nota de corte de 07 pontos e encontrou-se associação entre fazer acompanhamento em saúde mental e menores escores de sofrimento psíquico. Conclusão: Acompanhamento em saúde mental para os profissionais expostos à COVID é importante estratégia de enfrentamento para a sobrecarga e mudança na lógica de trabalho durante e após a pandemia, que parece estar associada a sofrimento psíquico.
Psychic distress of mental health workers in a pandemic context and associated factors
Keywords: Pandemics; Coronavirus infections; Mental health; Health personnel; Pandemias; Infecções por coronavírus; Saúde mental; Pessoal de saúde